Implementation of the Early Warning Score System in Monitoring Stroke Patients: Impact on Length of Stay and Patient Conditions upon Hospital Discharge - Waladani, Barkah; Santoso, Eko Budi; Suwaryo, Putra Agina Widyaswara (Babali Publisher, 2023)
Background: Stroke is a major health concern globally, necessitating effective monitoring tools for inpatient care. This research focuses on non-hemorrhagic stroke patients, aiming to evaluate the effectiveness of the Early Warning Score System (EWSS) in a hospital setting. Objective: The study seeks to assess changes in patient conditions, length of stay, and the impact of EWSS on monitoring non-hemorrhagic stroke patients. Results: The research findings reveal varying responses among patients, with the majority experiencing improvement, while a small number exhibited a decline in condition. Systolic blood pressure emerged as a sensitive parameter to changes, emphasizing the cardiovascular impact of non-hemorrhagic stroke. EWSS parameters predominantly remained normal, highlighting the system's efficacy in identifying early changes. Conclusion: The study contributes crucial insights, indicating that EWSS is an effective tool in monitoring non-hemorrhagic stroke patients. Patients with appropriate care demonstrated improvement, emphasizing the importance of continuous monitoring, particularly of blood pressure, in stroke management. These findings underscore the potential of EWSS in enhancing care, reducing hospital stays, and improving overall patient outcomes in non-hemorrhagic stroke cases. The study provides valuable implications for the strategic implementation of EWSS to elevate the quality of healthcare for stroke patients in hospital settings.